Revisiting the Connection between State Medicaid Expansions and Adult Mortality - Charles Courtemanche; Jordan Jones; Antonios M. Koumpias; Daniela Zapata (Institute of Labor Economics (IZA), 2022)
This paper examines the impact of Medicaid expansions to parents and childless adults on adult mortality. Specifically, we evaluate the long-run effects of eight state Medicaid expansions from 1994 through 2005 on all-cause, healthcare-amenable, non-healthcare-amenable, and HIV-related mortality rates using state-level data. We utilize the synthetic control method to estimate effects for each treated state separately and the generalized synthetic control method to estimate average effects across all treated states. Using a 5% significance level, we find no evidence that Medicaid expansions affect any of the outcomes in any of the treated states or all of them combined. Moreover, there is no clear pattern in the signs of the estimated treatment effects. These findings imply that evidence that pre-ACA Medicaid expansions to adults saved lives is not as clear as previously suggested.
Keywords: I13; I18; I38; 330; all-cause mortality; healthcare-amenable mortality; Medicaid; generalized synthetic control method; public health; healthcare reform